TANTANGAN PENDIDIKAN; UPAYA REPURIFIKASI PENDIDIKAN AKHLAQ ABAD 21 - moh zaini; Ahmad Barizi; Triyo Supriyatno; Marsuki Gani (IAIN Ambon, 2022)
The phenomenon of educational products in the 21st century is in two speculative positions; either beneficial or otherwise detrimental. For those who benefited technologically, he called it the century of brilliance. But for observers of values in the context of education, the 21st century is not only concluded as a challenge but even as an emerging threat to the process of moral growth, therefore it is necessary to find an alternative. The 21st century and the changing times that accompany it are unavoidable. Of course, this is a logical consequence. But value observers, especially academics, think about how the main anticipation is so that a value (akhlaq alkarimah) which is the main goal of Islamic education does not become the cost of changing times. This research was carried out with a qualitative library research approach, whose data sources were obtained from articles, news, and journals, using a documentary technique. Analyzed with a content analysis model. The results of this study provide an offer for repurposing moral education by reinforcing the pattern of education with a harmonious pattern of teachers and students, moral education with advice, re-orientation of learning goals and intentions instilled in students, learning by waro' (almost extinct in the educational process). ), learn istifadah, and learn by remaining steadfast so that the learner's soul remains strong in any situation.